CT‐measured skeletal muscle mass used to assess frailty in patients with head and neck cancer. Issue 5 (27th May 2019) - Zwart, Aniek T.; van der Hoorn, Anouk; van Ooijen, Peter M.A.; Steenbakkers, Roel J.H.M.; de Bock, Geertruida H.; Halmos, Gyorgy B.
Abstract: Background: Skeletal muscle depletion or sarcopenia is related to multiple adverse clinical outcome. However, frailty questionnaires are currently applied in the daily practice to identify patients who are potentially (un)suitable for treatment but are time consuming and straining for patients and the clinician. Screening for sarcopenia in patients with head and neck cancer (HNC) could be a promising fast biomarker for frailty. Our objective was to quantify sarcopenia with pre‐treatment low skeletal muscle mass from routinely obtained neck computed tomography scans at level of third cervical vertebra in patients diagnosed with HNC and evaluate its association with frailty. Methods: A total of 112 HNC patients with Stages III and IV disease were included from a prospective databiobank. The amount of skeletal muscle mass was retrospectively defined using the skeletal muscle index (SMI). Correlation analysis between SMI and continuous frailty data and the observer agreement were analysed with Pearson's r correlation coefficients. Sarcopenia was present when SMI felt below previously published non‐gender specific thresholds (<43.2 cm 2 /m 2 ). Frailty was evaluated by Geriatrics 8 (G8), Groningen Frailty Indicator, Timed Up and Go test, and Malnutrition Universal Screening Tool. A univariate and multivariate logistic regression analysis was performed for all patients and men separately to obtain odds ratios (ORs) and 95% confidence intervals (95% CIs). Results: The cohort included 82 men (73%) and 30 women (27%), with a total mean age of 63 (±9) years. The observer agreement for cross‐sectional measurements was excellent for both intra‐observer variability ( r  = 0.99, P  < 0.001) and inter‐observer variability ( r  = 0.98, P  < 0.001). SMI correlated best with G8 frailty score ( r  = 0.38, P  < 0.001) and did not differ per gender. Sarcopenia was present in 54 (48%) patients, whereof 25 (46%) men and 29 (54%) women. Prevalence of frailty was between 5% and 54% depending on the used screening tool. The multivariate regression analysis for all patients and men separately isolated the G8 questionnaire as the only independent variable associated with sarcopenia (OR 0.76, 95% CI 0.66–0.89, P  < 0.001 and OR 0.76, 95% CI 0.66–0.88, P  < 0.001, respectively). Conclusions: This is the first study that demonstrates that sarcopenia is independently associated with frailty based on the G8 questionnaire in HNC patients. These results suggest that in the future, screening for sarcopenia on routinely obtained neck computed tomography scans may replace time consuming frailty questionnaires and help to select the (un)suitable patients for therapy, which is highly clinically relevant.